2006
DOI: 10.1039/b512856k
|View full text |Cite
|
Sign up to set email alerts
|

Binding of monovalent metal cations by the p-sulfonatocalix[4]arene: experimental evidence for cation–π interactions in water

Abstract: Gibbs free energies, enthalpies and entropies for the binding of Na+, K+, Rb+, Cs+, Ag+, Tl+ and NH4+ by the p-sulfonatocalix[4]arene in water are determined by microcalorimetry. Whereas no significant heat effect is detected with Na+ or Ag+, suggesting that these cations are not complexed, weak but selective binding is observed with the other cations. The whole set of thermodynamic parameters, which demonstrate that the cations bind inside the cavity of the calixarene, evidence the importance of the cation-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 31 publications
3
66
2
5
Order By: Relevance
“…The PMF profile does not show any negative Gibbs free-energy minimum to suggest any favorable interaction between the caesium and the calixarene. This result is not in line with the recent experimental determinations [22,24] of the thermodynamic properties of binding of this cation by the psulfonatocalixarene. In what follows, we tend to include in the PMF calculation a quantum contribution which is likely to describe the different types of energy contributions of the cation-p interaction.…”
Section: Standard Pmf Calculationcontrasting
confidence: 59%
See 3 more Smart Citations
“…The PMF profile does not show any negative Gibbs free-energy minimum to suggest any favorable interaction between the caesium and the calixarene. This result is not in line with the recent experimental determinations [22,24] of the thermodynamic properties of binding of this cation by the psulfonatocalixarene. In what follows, we tend to include in the PMF calculation a quantum contribution which is likely to describe the different types of energy contributions of the cation-p interaction.…”
Section: Standard Pmf Calculationcontrasting
confidence: 59%
“…These calculations are based upon recent microcalorimetry and 133 Cs diffusion NMR spectroscopy experiments [22,24] which have shown that Cs + binds inside the cavity of the calixarene and that the association process is enthalpy driven due to favorable cation-p interactions. The PMF profile calculated from a standard model [38] does not predict any Gibbs free energy minimum, suggesting, in contrast to the experimental observations, that the cation is not complexed by the calixarene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[256] Die Bindung von Cs + an p-Sulfonatocalix [4]aren wurde mithilfe von 133 Cs-Diffusions-NMR-Spektroskopie [257] untersucht, wobei eine Bindungsaffinität von K a = (22 AE 9) m À1 in wässriger Lösung ermittelt wurde, in guter Übereinstimmung mit Werten von 1 H-NMR-spektroskopischen Titrationen [257] und mikrokalorimetrischen Techniken. [258] Mikrokalorimetrische Studien der Bindung verschiedener Metallionen an pSulfonatocalix [4] [259] Pyrogallol [4]arene fungieren auch als Rezeptoren für Alkalimetallkationen, besonders K + , Cs + und Rb + , wie kristallographisch gezeigt wurde. [260] Ca 2+ -Indol-Wechselwirkungen wurden 13 C-NMR-und CD-spektroskopisch im Kontext der Entwicklung Trp-basierter fluoreszierender Chemosensoren für das Metallion untersucht (Abbildung 27 a).…”
Section: Angewandte Chemieunclassified